LEGAL REGULATION OF THE SUBJECTS OF AVIATION ACTIVITIES - Похиленко, Ірина Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article is to determine peculiarities of the aviation activity and, on the basis of the analysis of legal literature and normative legal acts, to propose an author’s definition of the said concept. Research methods: the following methods are applied. Formal-logical – for the formation of new concepts, their classification; eliminating inaccuracies and contradictions, etc. Formal dogmatic, or legal method, based on the use of rules of formal logic for knowledge of law, is a traditional, inherent in legal science, since it proceeds from its nature. Its essence is in the formulation and disclosure of legal concepts, the construction of legal structures, and clarification of the actual content of the law. At all stages of scientific research the dialectical method is used. This method determines the paths of any scientific study. It helps to explore all the phenomena in the relationship, interdependence. Comparative method involves comparing single-order legal concepts, phenomena and processes to establish similarities and account for differences between them. Results: based on the analysis of legal literature and the current national, aviation legislation, the author suggested his own definition of the subject of aviation activity. The subject of aviation activity is physical and legal entities of any organizational and legal form and departmental subordination, which create conditions and use airspace with the help of aircraft and other fly machine, including air traffic services, airspace management and flow management, air traffic, which is performed safely, economically and efficiently by providing facilities and continuous service in cooperation with all parties and with the involvement of airborne and ground functions, act on the basis of the provisions of general and special aviation legislation and are able by their actions to acquire rights and exercise them independently, as well as to perform duties and be liable in case of non-compliance. Discussion: features of functioning of subjects of aviation activity, problems of classification of subjects of aviation activity.